2020
DOI: 10.3390/inorganics8110059
|View full text |Cite
|
Sign up to set email alerts
|

Toward Overcoming the Challenges in the Comparison of Different Pd Nanocatalysts: Case Study of the Ethanol Oxidation Reaction

Abstract: Precious metal nanoparticles, in particular palladium nanomaterials, show excellent catalytic properties and are key in the development of energy systems. For instance, ethanol fuel cells are promising devices for sustainable energy conversion, where Pd-based catalysts are key catalysts for the related ethanol oxidation reaction (EOR). Pd is a limited resource; thus, a remaining challenge is the development of efficient and stable Pd-based catalysts. This calls for a deeper understanding of the Pd properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Comparing NPs obtained by different methods remains a general challenge because the NPs are often characterized by different protocols using, for instance, different electrolyte concentrations, different EtOH concentrations for the EOR, different upper and lower limit potentials, different scan rates, different numbers of scans, different pretreatments in general, and different ink formulations in the case of supported electrocatalysts, not to mention that different normalizations are used to report the results, etc. 27,49,87 Nevertheless, the activity achieved here is relatively high for Au x Pd y catalysts 88,89 or comparable to that reported elsewhere but using more complex synthetic approaches. 85 In this respect, the readily active NPs obtained here by a simple method can be envisioned as a promising reference material for future studies across different laboratories for improved comparative studies.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…Comparing NPs obtained by different methods remains a general challenge because the NPs are often characterized by different protocols using, for instance, different electrolyte concentrations, different EtOH concentrations for the EOR, different upper and lower limit potentials, different scan rates, different numbers of scans, different pretreatments in general, and different ink formulations in the case of supported electrocatalysts, not to mention that different normalizations are used to report the results, etc. 27,49,87 Nevertheless, the activity achieved here is relatively high for Au x Pd y catalysts 88,89 or comparable to that reported elsewhere but using more complex synthetic approaches. 85 In this respect, the readily active NPs obtained here by a simple method can be envisioned as a promising reference material for future studies across different laboratories for improved comparative studies.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…We also showed that the solvent from the synthesis can be recycled several times. In our latest development, the synthesis could be performed at room temperature, ,, and a strong influence of the reducing properties of the solvent was shown . Pt has been the most studied material, and size controlled was achieved using alcohol/water mixtures.…”
Section: Colloidal Surfactant-free Synthesesmentioning
confidence: 99%
“…[10][11][12] At present, Pd-based nanomaterials are considered as one of the most effective EOR catalysts with excellent catalytic activity. [13][14][15][16][17][18][19] Nevertheless, the carbonaceous intermediates produced during the EOR will be adsorbed on the surface of Pd-based catalysts, which will reduce the catalytic performance. [20][21][22][23] Therefore, the development of durable Pd-based catalysts with high activity and efficiency is very important for the EOR.…”
Section: Introductionmentioning
confidence: 99%